Odpowiedź:
a)
- 3,5x = 7
3,5x = - 7
x = - 7 : 3,5 = - 2
b)
- 2,5x = x - 4
- 2,5x - x = - 4
- 3,5x = - 4
3,5x = 4
x = 4 : 3,5 = 4 : 35/10 = 4 : 7/2 = 4 * 2/7 = 8/7 = 1 1/7
c)
0,5y - 7 = y + 9
0,5y - y = 9 + 7
- 0,5y = 16
0,5y = - 16
y = - 16 : 0,5 = - 32
d)
- 2d - 1/2 = 1/2 | * 2
- 4d - 1 = 1
- 4d = 1 + 1 = 2
4d = - 2
d = - 2/4 = - 1/2
e)
- 3 1/3w = 8
- 10/3w = 8 | * 3
- 10w = 3 * 8 = 24
10w = - 24
w = - 24/10 = - 2,4
f)
- 3/5c = - 2c - 11 | * 5
- 3c = - 10c - 55
- 3c + 10c = - 55
7c = - 55
c = - 55/7 = - 7 6/7
g)
4x + 0,3 = 1/2x | * 2
8x + 0,6 = x
8x - x = - 0,6
7x = - 0,6
x = - 6/10 : 7 = - 3/5 * 1/7 = - 3/35
h)
0,2y - 6 = 0,7y + 11
0,2y - 0,7y = 11 + 6
- 0,5y = 17
0,5y = - 17
y = - 17 : 0,5 = - 34
Szczegółowe wyjaśnienie: